Targets and Mechanisms of Geminivirus Silencing Suppressor Protein AC2 - Veluthambi, Karuppannan; Sunitha, Sukumaran (Frontiers in Microbiology, 2021)
Geminiviruses are plant DNA viruses that infect a wide range of plant species and cause significant losses to economically important food and fiber crops. The single-stranded geminiviral genome encodes a small number of proteins which act in an orchestrated manner to infect the host. The fewer proteins encoded by the virus are multifunctional, a mechanism uniquely evolved by the viruses to balance the genome-constraint. The host-mediated resistance against incoming virus includes post-transcriptional gene silencing, transcriptional gene silencing and expression of defense responsive genes and other cellular regulatory genes. The pathogenicity property of a geminiviral protein is linked to its ability to suppress the host-mediated defense mechanism. This review discusses what is currently known about the targets and mechanism of the viral suppressor AC2/AL2/Transcriptional activator protein (TrAP) and explore the biotechnological applications of AC2.